SAĞLIKLI VE RİNİT’Lİ HASTALARDA METAKOLİN PROVOKASYONU İLE NAZAL HİPERREAKTİVİTENİN DEĞERLENDİRİLMESİ - TAHAMİLER, Rauf; ÇANAKÇIOĞLU, Salih (Cerrahpaşa Medical Journal, 2019)
Background and Design.- In the present study, metacholine power is investigated for the trigger of nasal hyperreactivity and achievement of healthy-ill selection at the 97 diseased and 20 healthy person. After provocation, there was no significant difference in NAR (nasal airway resistance) measurements between control and patient groups (p>0.05). There was a correlation between NAR measurement and score at the end of the provocation. There was no significant positive provocation level in any groups with metacholine provocation. Achievement of healthy-ill selection of the metacholine is inadequate because of that the increment of the NAR measurements was also seen at the healthy control group. Metacholine could not trigger a significant nasal reactivity increment.